Androgen receptor expression and response to chemotherapy in breast cancer patients treated in the neoadjuvant TECHNO and PREPARE trial - Witzel, Isabell; Loibl, Sibylle; Wirtz, Ralph; Fasching, Peter A.; Denkert, Carsten; Weber, Karsten; Lück, Hans-Joachim; Huober, Jens; Karn, Thomas; Mackelenbergh, Marion von; Marmé, Frederik; Schem, Christian; et al. (British journal of cancer, 2019)
The androgen receptor (AR) is discussed as a prognostic and/or predictive marker in breast cancer patients. AR mRNA expression was analysed by RT-qPCR in breast cancer patients treated in the neoadjuvant TECHNO (n  =  118, HER2-positive) and PREPARE trial (n  =  321, HER2-positive and -negative). In addition, mRNA expression of the AR transcript variants 1 (AR1) and 2 (AR2) was measured. Regarding subtypes, high AR mRNA levels were frequent in HER2-positive (61.3%, 92/150) and luminal tumours (60.0%, 96/160) but almost absent in triple-negative tumours (4.3%, 3/69) (p < 0.0001). Overall, high AR mRNA levels were found to be associated with lower pathological complete remission (pCR) rates (OR 0.77 per unit, 95% CI 0.67-0.88, p  =  0.0002) but also with better prognosis in terms of longer disease-free survival (DFS) (HR 0.57, 95% CI 0.39-0.85, p  =  0.0054) and overall survival (OS) (HR 0.43, 95% CI, 0.26-0.71, p  =  0.0011). In the PREPARE trial, a survival difference for patients with high and low AR1 mRNA levels could only be seen in the standard chemotherapy arm but not in the dose-dense treatment arm (OS: HR 0.41; 95% CI 0.22-0.74 vs. HR 1.05; 95% CI 0.52-2.13; p  =  0.0459). We provide evidence that AR mRNA predicts response to chemotherapy in breast cancer patients.